ESTIMATION OF WORKING CONDITIONS IN FOUNDRY SHOPS ON THE TOTAL MORBIDITY OF THE WORKERS - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия)
Estimation of working conditions influence on total morbidity of the workers in foundry is given. The results of analysis of morbidity of the workers in casting houses with different production types are given.